2006
DOI: 10.1177/0885066605285223
|View full text |Cite
|
Sign up to set email alerts
|

Off-label Reports of New Biologics: Exciting New Therapy or Dubious Research? Examples From Recombinant Activated Factor VII

Abstract: Although clinicians using drugs off-label would likely claim that such use is not "investigation,"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…It has been suggested that the use of rFVIIa for non-approved indications such as ICH be reserved to Institutional Review Board approved randomized controlled trials. 34 This would ensure that patients and next of kin are given adequate informed consent regarding the risks versus benefits of therapy. This recommendation has also been echoed in the 2007 ICH guidelines, which recommend against the use of rFVIIa outside the context of a clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the use of rFVIIa for non-approved indications such as ICH be reserved to Institutional Review Board approved randomized controlled trials. 34 This would ensure that patients and next of kin are given adequate informed consent regarding the risks versus benefits of therapy. This recommendation has also been echoed in the 2007 ICH guidelines, which recommend against the use of rFVIIa outside the context of a clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that the administration of off-label rf-VIIa in the operating room could help to identify a persistent surgical bleeding source or respond to eventual thrombotic complications at the surgical site. Further randomized controlled studies are mandatory to regulate the use of this potent but potentially harmful drug, as was emphasized in a recent review article on off-label use of new biologics (26). …”
Section: Discussionmentioning
confidence: 99%
“…tranexamic acid or fibrinogen concentrates). These observational reports are prone to patient selection bias and observer bias as the treatment is not masked and lack generalisability (Dzik, 2006). Interpretation of the effect of rFVIIa in refractory bleeding is further hampered by the complex coagulopathy that exists in these situations and the multiple blood components, blood products and potentially haemostatic drugs administered concurrently with rFVIIa.…”
Section: Summary Of Benefits Of Rfviiamentioning
confidence: 99%